SURFACE STRATEGY TAXONOMY ON THE EFL STUDENTS COMPOSITION A STUDY OF ERROR ANALYSIS - Suhono Suhono (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2016)
This study deals with error analysis on composition written by EFL Students IAIM NU Metro. It aims at developing further analyzing of error analysis in second language learners. For this purpose, an empirical study was conducted, using Indonesian students learning English as the subject of research. To achieve this purpose, the researcher explored the type of grammatical errors made by students at different grade semesters: the second, the sixth, and the eighth. More specifically, this study was an attempt to describe the type of grammatical error which frequently exist in written composition, to describe frequency grammatical error among the grade semesters, and to describe the sources of errors. Students’ writings were analyzed based on surface strategy taxonomy theory. The results of this research revealed that 268 sentences indicated errors. In all semesters, types of omission error was the highest one 131 (48.9%) sentences. Furthermore, grammatical error in the second semester was the highest one 124 (46.8%) sentences. The sources of errors of this research were mother-tongue influence (Interlingual errors). It was influenced by the native language which interferes with target language learning. The second was Intralingual errors, caused by the target tself like, misanalysis (wrong hypothesis), incomplete rule application. Keywords: Surface Strategy Taxonomy, Error Analysis, IAIM NU Metro.